Why South Africa Is Cheap for the Rich and Expensive for the Poor : Reconsidering the Balassa-Samuelson Effect - Dadam, Vincent; Hanusch, Marek; Viegi, Nicola (World Bank, Washington, DC, 2019)
This paper investigates cross-sectoral productivity differentials in South African industry and their distributional consequences. The analysis shows that typically, traded sectors have experienced low productivity growth over the past decade, while skill intensive service sectors have had significant productivity growth. This is the inverse of the traditional Balassa-Samuelson sectoral transformation hypothesis, where high wages in high-productivity traded sectors increase wages throughout the economy, thus increasing prices on non-traded goods and revaluing the country's real exchange rate. Instead, the higher productivity of non-traded sectors experienced in South Africa induces a devaluation of the real exchange rate and a contraction of the traded sectors. The results of the estimation show evidence of this "inverse" Balassa-Samuelson effect for agriculture and manufacturing and in particular mining. This "inverse" Balassa-Samuelson effect has important distributional consequences: the high-productivity sectors are associated with cheaper goods and services for wealthy households. This in turn burdens poor households, which are more dependent on traded goods, with higher prices, which are a consequence of low productivity and high markups.